2017
DOI: 10.1002/chem.201702276
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Catalyzed Olefin Metathesis with Low‐Valent Iron Alkylidenes

Abstract: Inspired by recent reports of low-valent iron-complex-catalyzed formal [2+2] cycloaddition of olefins, we demonstrate computationally that with such low-valent iron complexes and with "strong" ligands, the olefin metathesis is also preferred over the undesired cyclopropanation side-reaction, competition already studied by Hoffmann and co-workers almost 40 years ago (J. Am. Chem. Soc. 1981, 103, 5582). The [2+2] cycloaddition step in metathesis propagation, which gives a Chauvin-type metallacyclobutane intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 58 publications
0
31
0
Order By: Relevance
“…[64] However, some theoretical studies showed the possibility of low valent Fe-catalyzed OM. [73,75] Finally, apply rigid chelating ligands to control the geometry of the alkylidene and metallacycle to favor singlet states for both. [70,73,76] Scheme 16.…”
Section: Theoretical Studies and Challenges Of Fe-catalyzed Ommentioning
confidence: 99%
See 1 more Smart Citation
“…[64] However, some theoretical studies showed the possibility of low valent Fe-catalyzed OM. [73,75] Finally, apply rigid chelating ligands to control the geometry of the alkylidene and metallacycle to favor singlet states for both. [70,73,76] Scheme 16.…”
Section: Theoretical Studies and Challenges Of Fe-catalyzed Ommentioning
confidence: 99%
“…Third, use Fe(IV) complexes because, according to Hückel calculations, cyclopropanation is forbidden for d 4 metal centers [64] . However, some theoretical studies showed the possibility of low valent Fe‐catalyzed OM [73,75] . Finally, apply rigid chelating ligands to control the geometry of the alkylidene and metallacycle to favor singlet states for both [70,73,76] …”
Section: Ironmentioning
confidence: 99%
“…A mechanism explaining these experimental facts suggests three simultaneous processes: oligomerization, isomerization and metathesis catalyzed by iron bisiminopyridine complex. Later several theoretical and computational studies [62,63] established that iron catalysts have a high potential in the reaction of olefin metathesis.…”
Section: Formation Of Odd Carbon Number Olefinsmentioning
confidence: 99%
“…47, 51 On the other hand, investigations of cyclopropanations with formally ferric iron-porphyrins suggest in situ reduction of the metalloporphyrin and thus the active role of Fe II -porphyrin carbene in these reactions. 29, 32, 36 Computationally, several different mechanisms have been proposed for metal carbene cyclopropanations, including elimination from metallocyclobutane 6062 and addition via both concerted 6365 and step-wise 66, 67 pathways. Since both the metal center and ligand environment greatly influence the operating mechanism, it is critical to study the mechanism in newly developed systems such as the hemoprotein and Fe II -porphyrin based catalysts investigated here.…”
Section: Introductionmentioning
confidence: 99%